2013
DOI: 10.1111/bjd.12564
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the association of dermatomyositis and polymyositis with cancer

Abstract: SummaryBackground Although some features of dermatomyositis (DM) and polymyositis (PM) have been reported as possible prognostic indicators for cancer development, previous studies were small in size and were unable to establish a definitive relationship between neoplasms and DM and PM. Objectives To evaluate risk factors for developing malignancies in patients with DM and PM. Methods Meta-analysis of the studies reported in the literature was performed to unveil risk factors for developing cancer among patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
53
1
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 36 publications
(59 reference statements)
11
53
1
13
Order By: Relevance
“…According to a recent meta-analysis, factors associated with a paraneoplastic etiology of myositis include advanced age, male gender, skin necrosis, and dysphagia [104]. Detection of anti-155/140-Abs in cases with negative classical Abs (anti-Jo-1, anti-PM-Scl, anti-U1-RNP, anti-U3-RNP, anti-Ku) is in 94 % associated with a paraneoplastic origin [105].…”
Section: Paraneoplastic Myositismentioning
confidence: 99%
“…According to a recent meta-analysis, factors associated with a paraneoplastic etiology of myositis include advanced age, male gender, skin necrosis, and dysphagia [104]. Detection of anti-155/140-Abs in cases with negative classical Abs (anti-Jo-1, anti-PM-Scl, anti-U1-RNP, anti-U3-RNP, anti-Ku) is in 94 % associated with a paraneoplastic origin [105].…”
Section: Paraneoplastic Myositismentioning
confidence: 99%
“…Sarı tırnak sendromu (STS) nadir görülen, klasik triadını lenfödem, plevral efüzyon ve sarı tırnağın oluşturduğu bir tablodur. STS, idiyopatik olabilmesinin yanı sıra bazı malignitelerde paraneoplastik bir bulgu olarak da bildirilmiştir 12,13 . Yine de birçok paraneoplastik bulgu kadar güçlü bir belirteç değildir 13 .…”
Section: Tırnak Sarı Tırnak Sendromu (Sts)unclassified
“…Çoğu vakada 20 tırnak birden tutulur 2 . Mevcut malignitenin tedavisi ile STS'nda düzelme olması da paraneoplastik ilişkiyi desteklemekle birlikte 12 , her zaman tümör tedavisi ile gerileme olmayabilir 13 . Edinsel STS, malignite dışı durumlarda da görülebilir (Tablo 1).…”
Section: Tırnak Sarı Tırnak Sendromu (Sts)unclassified
“…This is the first report of the association of amyopathic DM with an adenocarcinoma of the uterus. Studies have consistently demonstrated a DM-associated risk of malignancy, especially in the elderly and within three years of the first DM diagnosis [1]. Patients with DM including the amyopathic sybtype in association with and as a non-metastatic effect of ovarian cancer or other solid tumors of the female reproductive tract have been described but very rarely with either a carcinoma or a sarcoma of the uterus [3,4].…”
mentioning
confidence: 99%